THINK PAIR SHARE: ALTERNATIF PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA - Rita Sari; Nuraida Nuraida; Shafira Rizki (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2017)
The action research figured out about the effectiveness exploration of a new alternative in Think Pair Share (TPS); with Kemmis & Taggart Model, for science, Ilmu Pengetahuan Alam (IPA) subject. The research cycled the TPS within listening, observing, mentality, emotionality, and motoric activity. First of all, the cycle I signified that the students have lower inquiry in mentality. It had been observed on the lower frequency of asking-giving opinion portions. Secondly, the cycle II signified that there is a not slightly difference of inquiry, however, the students indicated response more than the previous cycle. The third cycle signified a response to the executed activity. It projected students’ determination and enthusiastic in asking-giving opinion within the activity. The cycles mean score estimated 65 for the first one, increased to 74 in the second cycle, and reached 85 in the last cycle. The students’ achievement stimulated the test instruments significantly. In conclusion, the action research about the new alternative in TPS; with Kemmis & Taggart Model proves effective to SD Negeri Gampong Teungoh, Kota Langsa. It is suggested to be applied in science for elementary school subjects as one of the teaching techniques. Keywords: Think Pair Share, learning Activity, and Students’Achievements.